The Relationship between Career Satisfaction and Life Satisfaction: An Investigation from the Perspective of Efficacy of Football Coaches in Türkiye - Anıl Siyahtaş; Ebru Ceviz (CV. FOUNDAE, 2025)
Background: Career and life satisfaction are critical factors influencing football coaches' well-being, performance and future. However, the role of coaching efficacy as a mediator between these two factors remains underexplored, particularly in the context of football coaching in Türkiye.Aims: The present study examines the mediating role of coaching efficacy in the relationship between football coaches' careers and life satisfaction.Methods: The research group, which adopted a quantitative approach, consists of individuals with football coaching licences in Türkiye (n=429). The parametric tests were used in the analyses, and a modern approach was adopted for the mediation analysis. Furthermore, ANOVA was applied to the analysis of differences, and the Pearson correlation test was applied to the relationship between concepts. In addition, the difference between the groups was determined by the Tukey test.Result: The age factor did not affect coaching efficacy. However, experience and license categories were found to be important factors. The structural model constructed for the research was confirmed (Δχ²/sd=1.94; RMSEA=.05; CFI=.95; GFI=.90; IFI=.94).Conclusion: The study determined that coaching efficacy mediated the relationship between coaches' career and life satisfaction. Coaching efficacy plays an important role not only for the athletes but also for their own lives. Therefore, it is recommended that football coaches give importance to professional efficacy and improve themselves to achieve career and life satisfaction.